Teaching and learning partnerships in higher education: Using students' feedback to inform developments in teaching. - Scott, Shelleyann; Dixon, Kathryn; Dixon, Robert (AARE Inc, 2005)
University administrators are becoming aware of the importance of increasing the quality of teaching and learning across their study programs. Measuring and supporting quality teaching and learning is frequently linked with accountability to internal and external stakeholders. The increasing pressures on Australian universities to be more strategic with a view to enhancing market share in a competitive educational industry has put pressure on all key players in the process to investigate ways in which the quality of learning can be improved. The partners in learning within this research involve the students, lecturers, and the organisation. This research investigates the ‘student feedback’ data (UEQ) in a Business Division in an Australian University. Data is collected and analysed by an external department to the Schools and educators within this department are available to work with academics to interpret their results. Student feedback data indicates that the business school academics must engage with teaching and learning issues such as workload, increasing the quality of teaching and assessments, and clarifying expectations. The study identifies a number of key initiatives which serve as a model for facilitating a constructive response to the current political and economic pressures within the context of higher education in Australia.